(untitled) (Indian Journal of Arid Horticulture, 2025)
The present study was carried out at Krishi Vigyan Kendra-Panchmahals district of central Gujarat during 2012-13. One of the major constraints of traditional bottle gourd farming is low productivity because of non-adoption of advanced technologies. The lack of suitable HYVs (High Yielding Varieties), technical knowledge, quality irrigation water and awareness with respect to use of protection measures were found to be the major constraints in bottle gourd production. To increase the production, productivity and quality of bottle gourd, Front Line Demonstrations were conducted at various farmers’ field. All the recommended practices were provided to the selected farmers. Results of the study revealed that the improved variety of Bottle Gourd cv. Pusa Naveen recorded the higher average yield (273 q/ha) as compared to local check (235 q/ha) traditionally grown by the farmers. The percentage increase in the yield over local check (padara bottle gourd) and demonstration (Pusa Naveen) 16.17 was recorded. The technological gap in terms of productivity (17.0 q/ha) were computed. The technology index values 5.86% was recorded. By adopting Bottle Gourd cv. Pusa Naveen along with improved production technologies, yield can be increased upto a great extent. This will substantially increase the income as well as the livelihood of the farming community.